Implementation of the Function of Maximizing the Security Level in the Administration of Justice in the Digital Economy - Valeev, Damir Khamitovich; Nuriev, Anas Gaptraufovich (Cuestiones Políticas, 2020)
The research analyses the implementation of the role of maximizing the level of security in the administration of justice in the context of the digital economy. Methodologically, the documentary observation research technique and, to process sources, sociological-dialectical analysis were used. Digitization as a transformational factor of many branches of social relations implies dependence on the implementation of a series of interdependent legal facts with digital technologies so that the action has a legal and concrete result. The digital level as a new platform for the implementation of a number of public functions posing new challenges for the public administration system and also determines the status of new functions that can provide a "digital future" with a positive development dynamic. Conclusion mode everything indicates that, these new functions can be austable in order to maximize security in the implementation of public functions in response to new threats. Particularly sensitive is the area of justice administration, which is also actively introducing many digital tools into the case-resolution process.